3ES (EXPLORE ENLIGHTEN EXERCISE) LEARNING WORKSHEET: ITS’ EFFECTS TO THE ACADEMIC PERFORMANCE IN IDENTIFYING RESEARCH PROBLEMS AMONG SENIOR HIGH SCHOOL - PRESTOZA, MARK-JHON (International Journal of Arts, Sciences and Education, 2022)
This study focused on the Effect of 3Es (Explore, Enlighten, and Exercise) Learning Worksheet on the academic performance of the student in identifying research problems among Senior High School students. Specifically, it aimed to determine the Effect of the 3Es Learning Worksheet on the student's performance in identifying the research problem, the pre-assessment and post-assessment results of the group before and after implementing the intervention, and the effect size of the intervention on the academic performance of the participants. This study utilized 54 participants of the group using – shoot test utilizing total enumeration. The researcher used Pre – Experimental research design, specifically the Pre – Assessment - Post Assessment Only Design, wherein the subjects were randomly assigned to the group. The following findings and conclusions were drawn from the study; the students quickly identify and justify research problems using the Learning Worksheet using the 3Es Learning Worksheet. There is a significant increase in the post-assessment on the students' performance in identifying the research problem. There is a considerable difference in the academic performance of the group before and after the intervention. It is evident that the students performed better; thus, the intervention is effective. From the light findings and conclusion, the researcher would like to recommend that the teacher particular research teacher and teacher who are using an inquiry-based learning approach adopt the 3Es Learning Worksheet as this has been proven to be useful in identifying a problem that is an empirical base. The result must be disseminated through LAC sessions, meetings, and research fora. The same line of the study must be conducted to other tracks or strands.